Active participation of mothers in plastic recycling activities to improve water quality and reduce environmental pollution - Jessica Elfani Bermuli; Kurnia Putri Sepdikasari Dirgantoro; Pingkan Imelda Wuisan; Year Rezeki Patricia Tantu; Henni Sitompul; Figlio Guardino Loho; Grace Niche Agnesa Silaban (Universitas Muhammadiyah Malang, 2025)
This program investigates active participation of mothers in plastic recycling activities to improve water quality and reduce environmental pollution through the creation of ecobrick. Implemented as a community service program, the initiative followed a structured approach encompassing observation, education, assistance, and evaluation stages. The program aimed not only to minimize plastic waste but also to empower residents with skills and knowledge for sustainable environmental management. Throughout the program, participants showed high levels of enthusiasm and engagement, actively collecting and compacting various types of plastic waste into ecobrick. The program outcomes indicate significant gains in both technical competencies related to ecobrick production and increased environmental awareness among participants, fostering a sense of ecological responsibility and community collaboration. Evaluation results demonstrate the program’s effectiveness in reducing the amount of unmanaged plastic waste and contributing to a cleaner neighborhood environment. This success also supports the broader goal of Sustainable Development Goal (SDG) 6, specifically focusing on clean water and sanitation by addressing pollution sources within the community. The findings underscore the potential of community-led initiatives in achieving sustainable environmental impact, suggesting the scalability of this program model to similar urban and suburban areas facing plastic pollution challenges.